Linguistic Polyphony in the 2018 Costa Rican Presidential Elections: Deciphering the Web of Citizens’ Voices and Points of View - Arroyo-Mata, Marco A. (2023)
The interview is a discourse practice that represents a version of the world through subjective, as well as evaluative mechanisms. As a research instrument, it allows us to know the different representations of individual realities from the perspective of common citizens. Therefore, for this article, we determined the linguistic patterns present in the dialogic positionings of interviews about the 2018 Costa Rican elections, conducted throughout the country. For the sampling, men and women from different geographical areas, ages, educational levels and political affiliations were included. Using a reworking of the linguistic categories of the engagement system of the appraisal theory and the approaches of the Scandinavian Theory of Linguistic Polyphony (ScaPoLine), we analyzed the polyphonic mechanisms and polyphonic strategies of the dialogic utterances emitted by the interviewees. It was established that there is a preference for incorporating other people's positions and points of view by using polyphonic strategies that open discursive spaces to non-authorial voices and do not limit their scope. In addition, there was a preference for using syntactic polyphonic structures (negations, concessions, reported speech, evidentials), rather than their lexical counterparts.